Chronology and documentary handbook of the State of Arizona. - Trover, Ellen Lloyd (Chronologies and documentary handbooks of the States, 1972)
Contains a chronology of historical events from 1526 to 1970, a directory of political figures, an outline of the State constitution, and copies of five historical documents.